The Influence of Product Quality and Price on Repurchase Intention among Sempol Kasa MSME Customers - Prayoga, Bima; Setyawan, Edy; Sudrajat , Anton (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
The increasingly advanced business world has led to increased competition. In this case, consumers play a key role in determining the products they desire, thus ensuring quality. product is matter Which important And need noticed Every company wants to get maximum results and be able to compete. in market. factor determinant Which influence interest repurchase Among these factors, product quality and price are factors that can determine whether customers will repurchase. The aim of this study is to determine the extent of the influence quality product And price to repurchase customers at the Sempol Kasa MSME. The method used in this study is a quantitative research method. The results of the study show that partially Product Quality has a positive and significant effect on repurchase of Sempol Kasa MSME customers with a coefficient value of 0.270 and a significance value of 0.000 < 0.05. And Price influential positive and significant impact on repurchase of Sempol Kasa MSME customers with a coefficient value of 0.366 and a significance value of 0.000 < 0.05. simultaneous quality Product and Price has a positive and significant effect on repurchase, the significance value is 0.000, less than 0.05. After testing the coefficient of determination, the Adjusted R square value is known. as big as 0.632 so own meaning that variables Quality Product and Price simultaneously have an influence of 63.2% on Repurchase customer MSMEs Sempol Gauze And the remaining 36.8% is influenced by other variables outside this study.